One pot hydrogenation of furfural to 2-methyl tetrahydrofuran over supported mono- and Bi-metallic catalysts - Date, Nandan S.; Hengne, Amol M.; Huang, K. -W.; Chikate, Rajeev C.; Rode, Chandrashekhar V. (ChemistrySelect, 2020)
2-Methyltetrahydrofuran is a valuable commercial product that can be obtained by direct hydrogenation of furfural. In the present study, among several carbon supported bimetallic Ir-Ni catalysts with different loadings screened, 4% Ir-4% Ni/C catalyst showed excellent activity in terms of direct conversion (99%) to 2-MeTHF with a maximum selectivity of similar to 74% at 220 degrees C and 750 psig, suppressing the formation of side chain as well as ring opening products. The catalytic activity was found to be mainly affected by catalyst preparation methods, metal loadings, surface composition, temperature, pressure and catalyst loading. HR-TEM and STEM revealed well dispersed Ir-Ni NPs having the particle sizes in the range of 2 to 5 nm. Different phases of Ir i. e. Ir degrees and IrO(2)as well as oxygen vacancies were found to be responsible for hydrogenation of furfural to 2-methyl furan while, Ni degrees and NiO were responsible for further hydrogenation to 2-MeTHF. The synergic effect between Ir and Ni was established through XPS, H-2-TPR analysis. With the help of some control experiments, the plausible reaction pathway was also proposed. The catalyst prepared by co-impregnation method found more effective than prepared by sequential addition method. At lower Ni loadings of 1% and 2%, low temperature of 160 degrees C as well as at low H(2)pressure of 250 psig, mixture of furfuryl alcohol and 2-methyl furan were formed selectively. Catalyst could be successfully reused up to 3 times without leaching of metals.
Keywords: 2-Methyltetrahydrofuran; Bimetallic catalyst; furfural; Hydrogenation; OER type mechanism